Applying nature's design : corridors as a strategy for biodiversity conservation - Anderson, Anthony B. (Anthony Bennett), 1950-; Jenkins, Clinton N. (New York : Columbia University Press, 2006)
The fragmenting of habitats is endangering animal populations and degrading or destroying many plant populations throughout the world. To address this problem, conservationists have increasingly turned to biological corridors, areas of land set aside to facilitate the movement of species and ecological processes. However, while hundreds of corridor initiatives are under way worldwide, there is little practical information to guide their design, location, and management. Applying Nature's Design offers a comprehensive overview of current knowledge on corridors, their design, and their implementation. Anthony B. Anderson and Clinton N. Jenkins examine a variety of conceptual and practical issues associated with corridors and provide detailed case studies from around the world. Their work considers how to manage and govern corridors, how to build support among various interest groups for corridors, and the obstacles to implementation. In addition to assessing various environmental and ecological challenges, the authors are the first to consider the importance of socioeconomic and political issues in creating and maintaining corridors.
Frontmatter -- Contents -- Illustrations -- Acknowledgments -- 1. Introduction -- 2. Conceptual Foundations of Corridors -- 3. Corridor Design -- 4. Corridor Implementation -- 5. Case Studies -- Notes -- References -- Index.
Includes bibliographical references (pages 203-213) and index.
Print version record.
In English.
JSTOR
Keywords: Corridors (Ecology); Corridors écologiques.; SCIENCE -- Life Sciences -- Biological Diversity; NATURE -- Animals -- Wildlife; SCIENCE -- Environmental Science; Corridors (Ecology); Ecology; Landscapes; Design; Administrative management; Case studies; Natuurbehoud; Biodiversiteit; Habitat (ecologie); Corridors; Corridors écologiques.; Diversité biologique -- Conservation des ressources; Electronic books